CA 19-9 as a non-invasive marker for disease activity in hepatitis C patients : is there any role? - Hasmoni, Mohamed Hadzri; Jaafar, Khairul Azhar (Malaysian Medical Associations, 2008)
The combined elevation of tumor markers carbohydrate antigen 19-9 (CA 19-9)and carbohydrate antigen 125 (CA 125) has been shown to be associated with the severity of liver fibrosis in patients with liver disease. we assessed the association between CA 19-9 and viral hepatitis B activity which will allow us to know the usefulness of CA 19-9 as a surrogate marker for the disease activity in hepatitis B patients.